Isu Politik Identitas dan Dinasti Politik dalam Kampanye Pilkada Serentak Tahun 2020 - Ukhra, Aunil; Hijri, Yana Syafriyana; Taufikurrohman, Ifan (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study was intended to explain the phenomenon of identity politics and political dynasties in the holding of simultaneous elections in 2020. The focus of this study was looking at the issue of identity politics and political dynasties in several regions, including Solo, Medan, South Tangerang, and Central Kalimantan, which were case studies of identity politics and political dynasties issue in the 2020 elections. This research used a type of qualitative research with a descriptive approach. Data was obtained through literature studies by looking at previous research based on the same topic and news in the mass media about the issue of identity politics and political dynasties. The study found that identity politics and political dynasties still occurred in some regions, i.e., in Solo, Medan, South Tangerang, and Central Kalimantan. In addition, hate speech, black campaigns, and hoax issues had sprung up with different models through social media and billboards.